Traumatic Damage Pathomechanism of Cerebral Vessels Caused by Geriatric Changes - Wiczkowski, E.; Kędzia, A.; Kania, A. (Engineering Transactions, 2003)
The knowledge of mechanical properties of the brain blood vessels enables an assessment of pathological changes caused by human aging. As it results from our investigations, a greater elasticity of blood vessels in the occipital region accounts for the rare occurrence of subdural space blood clots in this region of the brain. Also, a map can be derived based on our results, of the most severe head trauma directions causing damages of blood vessels in the subdural space.